Serum ferritin level and red blood cell parameters in healthy controls and chronic periodontitis patients - S Latha; S Thirugnanamsambandan; R T Arun; K. M. K. Masthan; L Malathi; E Rajesh (Wolters Kluwer Medknow Publications, 2015)
Periodontitis, which is a chronic inflammatory disease causes reduction in the number of erythrocytes and hemoglobin. It is found to be caused by specific pathogenic subgingival plaque bacteria. Periodontitis is host mediated through release of pro inflammatory cytokines by local tissues and immune cells in response to bacterial flora and its products, especially lipopolysacharides. Periodontitis is found to have systemic effect and the cytokines produced inhibit proliferation and differentiation of erythrocytes leading to anaemia. This study evaluate level of hemoglobin erythrocytes, hematocrit and serum ferritin levels in healthy subjects and periodontitis patient.